ChemInform Abstract: Catalytic Use of Zinc Amide for Transmetalation with Allylboronates: General and Efficient Catalytic Allylation of Carbonyl Compounds, Imines, and Hydrazones. Issue 36 (15th August 2013) - Cui, Yi; Li, Wei; Sato, Takehiro; Yamashita, Yasuhiro; Kobayashi, Shu
Abstract This highly efficient reaction for the allylation of a variety of carbonyl derivatives is the first synthetic method using catalytic amounts of a zinc amide.